T-Cell Lymphopenia Detected by Newborn Screening in Two Siblings with an Xq13.1 Duplication - Rios, Xavier; Chinn, Ivan K.; Orange, Jordan S.; Hanson, Celine I.; Rider, Nicholas L. (Frontiers in Pediatrics, 2017)
Newborn screening for Severe Combined Immunodeficiency has proven successful in identifying infants with T-cell deficiencies before they become severely ill. Additionally, the newborn screen can detect subtle early phenotypes that may become severe later in life. We present the case of siblings with features suggestive of T-cell lymphopenia identified as having low T-cell receptor excision circles counts by newborn screening. Expanded immune testing showed robust lymphocyte mitogen and antigen responses with normal vaccine responses and immunoglobulin levels for both boys over time. Genetic analysis revealed an Xq13.1 duplication in each child not found in the mother. The variant is downstream of the IL2RG gene with potential regulatory significance, suggesting a mechanism for the T-cell lymphopenia. The newborn screen provided these patients heightened surveillance and patient-specific management, including delayed live vaccines and Pneumocystis jiroveci pneumonia (PJP) prophylaxis. Fortunately, the brothers have not suffered invasive or opportunistic infections and are well at ages three and four. In this report, we illustrate the challenges of managing seemingly asymptomatic immunodeficient patients without a definitive genetic diagnosis and show how unbiased genetic analysis can expand understanding about primary immunodeficiency phenotypes.